2016
DOI: 10.3892/etm.2016.3445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two GABA-ergic drugs on the cognitive functions of rapid eye movement in sleep-deprived and recovered rats

Abstract: Rapid eye movement (REM) sleep is closely associated with nervous functions. The present study aimed to evaluate the effects of gabazine and tiagabine on the cognitive functions (CF) of REM sleep-deprived and sleep recovered rats. Rats were divided into REM sleep deprivation, blank control (CC) and environmental groups. The REM sleep deprivation group was further divided into non-operation (nonOP), sham-operated (Sham), gabazine (SR) and tiagabine groups. Each group was evaluated over five time points: Sleep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The inhibitory effect of GABA on nerve cells is mainly achieved by stimulating the GABA A receptor (GABA A R), which is a drug target for benzodiazepines against insomnia, anxiety, and withdrawal symptoms (Gielen, Lumb, & Smart, 2012). Animal experiments have shown that increased GABA content in cerebrospinal fluid can prolong the sleep duration of cats (Gottesmann, 2002); whereas rats with rapid eye movement sleep deprivation have increased GABA content in the brain, which is considered an auto-regulatory mechanism of animals with sleep deficit (Bao, Si, Wang, Wuyun, & Bo, 2016). In sum, both clinical and animal experiments have demonstrated the therapeutic significance of increased GABA content in patients with sleep disorders (Scalise et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of GABA on nerve cells is mainly achieved by stimulating the GABA A receptor (GABA A R), which is a drug target for benzodiazepines against insomnia, anxiety, and withdrawal symptoms (Gielen, Lumb, & Smart, 2012). Animal experiments have shown that increased GABA content in cerebrospinal fluid can prolong the sleep duration of cats (Gottesmann, 2002); whereas rats with rapid eye movement sleep deprivation have increased GABA content in the brain, which is considered an auto-regulatory mechanism of animals with sleep deficit (Bao, Si, Wang, Wuyun, & Bo, 2016). In sum, both clinical and animal experiments have demonstrated the therapeutic significance of increased GABA content in patients with sleep disorders (Scalise et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the clinic, numerous subjects suffer from chronic insomnia. In order to investigate this condition, modified multiple separate platforms surrounded by water have been used to prepare acute sleep deprivation or chronic sleep restriction models in various studies (7)(8)(9)(10)(11). However, to the best of our knowledge, chronic sleep deprivation models involving modified multiple platforms have not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…DE-QI YAN 1 , XING-PING ZHANG 1,2 , WEN-HUI ZHANG 1 , NING DENG 1 , ZHENG-TING LIANG 1 , TAO LIU 2 , GUAN-YING WANG 1 , QIAN-WEI YAO 1 , KAI-KAI WANG 1 and ZHEN-PENG TONG 1 Modified multiple platforms surrounded by water have been frequently been utilized to deprive rats or mice of rapid eye movement (REM) sleep for 24-120 h (7)(8)(9)(10)(11). This method is mainly suitable for the preparation of acute insomnia models with 24 h sleep deprivation per day (12,13).…”
Section: Establishment Of a Chronic Insomnia Rat Model Of Sleep Fragm...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the CNS [23], IGF-1 is widely distributed in cortex, hippocampus and other brain regions closely related to cognitive function [24]. Previous studies have shown that mice exposed to sevo urane will present with spatial learning and memory ability impairment, but the addition of exogenous IGF-1 can improve this cognitive impairment [25]. In an animal model of traumatic brain injury, continuous lateral ventricle injection of IGF-1 for seven days after trauma led to neural restructuring and the movement function of mice and cognitive function were improved [26].…”
Section: Discussionmentioning
confidence: 99%